Experimental and numerical investigation of a novel vertically unconstrained steel inter-modular connection. (February 2023) - Bazarchi, E.; Davaran, A.; Lamarche, C.P.; Roy, N.; Parent, S.
Abstract: Modular constructions are off-site prefabricated structures with transportable units assembled on-site. These units are linked together using mechanical connectors called "inter-modular connections". Modular building structures are attractive from a constructional efficiency point of view if they include specific characteristics such as ease of on-site assembly and speed of construction. Accordingly, a vertically unconstrained inter-modular connection can considerably decrease the construction effort and promote the feasibility of the modular system if tension forces do not develop in columns when the structure is submitted to lateral loads. This study presents an efficient vertically unconstrained inter-modular connection, including a bolted tie plate and male–female components to ensure the connectivity of the diaphragms and columns. Two series of experimental tests are performed to examine the proposed inter-modular connection's shear and axial force responses. The calibrated finite element models developed in ABAQUS software are used to study the in-plane shear behavior of a perforated plate acting as horizontal component of the inter-modular connection. The results show that the proposed connection has adequate ductile ultimate strength controlled by the yielding of the net section of the tie plate. However, removing the up-lift constraining mechanisms may lead to serviceability issues due to a potential slip occurrence between modular components constructed with tolerances. The experimental and numerical results/frameworks presented herein provide detailed behavioral information, including slip, yielding, and failure modes of the connection's components. The captured behavior can be used to develop a simplified model of the proposed connection that can be used in detailed structural analyses. Highlights: Novel uplift unconstrained inter-modular connection is proposed. Uplift-unconstrained inter-modular connection can increase the construction speed. The components of the connection are investigated experimentally and numerically. Multi degree of freedom behavioral laws are proposed to model the connection. Equations are proposed to calculate the in-plane shear capacity of the tie plate.